Unraveling the Neurological Complexity of Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal Protein, and Skin Changes Syndrome: A Report of a Challenging Case of a Young Woman and Cutting-Edge Advancements in the Field - Gioconda Furciniti; Giuseppe Casalino; Francesco M. Lo Russo; Niccolò Bolli; Megi Meneri; Giacomo P. Comi; Stefania P. Corti; Daniele Velardo (Diseases, 2023)
POEMS syndrome—characterized by polyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes—is an uncommon and complex paraneoplastic disorder encompassing a diverse array of symptoms. Here we report the challenging case of a 34-year-old female who sought medical attention at the emergency department due to distal lower limb weakness. She was breastfeeding her first child at that time. Her condition rapidly deteriorated, making it difficult for her to perform simple tasks independently. Initially, she struggled with activities like jumping or climbing stairs. Eventually, her ability to walk was also compromised. These symptoms underscored the swift evolution of her polyneuropathy. Nerve conduction studies and electromyography confirmed a diagnosis of mixed demyelinating and axonal polyneuropathy. Subsequent investigations, including bone marrow biopsy and immunochemistry testing, revealed a plasma cell disorder characterized by lambda monoclonal gammopathy, along with elevated levels of vascular endothelial growth factor (VEGF > 8000 pg/mL). This pivotal finding led to the diagnosis of POEMS syndrome, prompting the initiation of antineoplastic therapy (daratumumab-lenalidomide-dexamethasone) to manage this condition. An autologous cell transplantation was planned. The rarity of POEMS syndrome and its diverse clinical manifestations often lead to an incorrect or delayed diagnosis. Our case underscores the importance of considering this syndrome in patients presenting with acute or subacute polyneuropathy, even if the patients are young. In conclusion, this case elucidates the diagnostic complexities of POEMS syndrome, emphasizing the integral role of comprehensive multidisciplinary evaluations and the potential influence of increased VEGF as a diagnostic key element and possible therapeutic target.